Efisiensi Penyisihan Logam Cr (VI) Menggunakan Biosorben Jamur Coprinus comatus Teraktivasi NaOH - Dispriana, Nurmala; Yenie, Elvi; Amraini, Said Zul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Metal Cr (VI) is a metal found in high concentrations of liquid waste electroplating, so it is toxic can cause acute and chronic poisoning. Using fungi biomass become an alternative to solving environment pollution problems caused by heavy metals. The research purposed to learn the ability of C. comatus fungi biosorbent to set aside the metal Cr (VI) through the process of biosorbent characterization with variations of activator NaOH 0,3; 0,5 and 0,7 N with activation time 15 minutes. Result of the research showed characterization phase of biosorbent obtained the best conditions in treatment activator NaOH 0,3 N with efisiensi removal 47,81 %.Keywords : C. comatus fungi, concentration activation, metal Cr (VI), electroplating liquid waste.